STUDI KRITIS FORMULASI KEBIJAKAN HUKUM PIDANA PADA RANCANGAN UNDANG-UNDANG PENGHAPUSAN KEKERASAN SEKSUAL - Sheila Maulida Fitri (Universitas Muara Bungo, 2021)
Sexual violence is the background for many people to demand special regulations governing these crimes in order to protect and legalize the procedure for fulfilling the rights of victims of immoral crimes based on the protection of human rights through the MCC Bill. This article intends to analyze the formulation of norms in the bill from the material and formal criminal law aspect in order to anticipate problems in the future. The research method used is normative juridical with a statutory and analytical approach. This article concludes that although the MCC Bill has new invention in the formal criminal law aspect in the form of norms governing procedures for handling sexual violence victims, however, there is duplication in the material criminal law aspects, especially regarding the classification types of crimes that are categorized as sexual violence.